Another Look at the Rhetorical Moves and Linguistic Realizations in International and Indonesian Journal Articles: A Case of Tourism Research - Kurniawan, Eri; Sabila, Nurul Aini Akrima (Indonesian Journal of Applied Linguistics, 2021)
Although a significant number of studies have been conducted to explore the rhetorical structures of research article abstracts, there is a paucity of research specifically comparing the move patterns, and linguistic features of tourism research article abstracts published in international and national journals. Such a comparison is quintessential to address a notion that journal indexation may factor into the quality of textual organization in abstract writing. Employing Hyland’s (2000) analytical framework, the paper analyzed 120 tourism research article abstracts from international journals indexed by Scopus and Indonesian journals indexed by Sinta. Findings revealed more similarities than differences across the two corpora. All of Hyland’s five moves were generally found in the abstracts, with M2 (Purpose), M3 (Method), and M4 (Product) as the most occurring moves in both data sets. An exception was found in M1 (Introduction) and M5 (Conclusion), where M1 was favored and M5 was excluded in Sinta-indexed abstracts, yet the reverse was true of Scopus-indexed counterparts. In terms of the linguistic features, present tense and active voice were evidently dominant across both data groups, with a notable exception in Method move, where past tense and passive voice were more favorable. These findings appear to suggest that journal indexation does not profoundly influence abstract writing. Recommendations and implications for academic writing for publication purposes are also discussed.